Collectin liver 1 and collectin kidney 1 and other complement‐associated pattern recognition molecules in systemic lupus erythematosus. (31st August 2015) - Troldborg, A.; Thiel, S.; Jensen, L.; Hansen, S.; Laska, M. J.; Deleuran, B.; Jensenius, J. C.; Stengaard‐Pedersen, K.
Summary The objective of this study was to explore the involvement of collectin liver 1 (CL‐L1) and collectin kidney 1 (CL‐K1) and other pattern recognition molecules (PRMs) of the lectin pathway of the complement system in a cross‐sectional cohort of systemic lupus erythematosus (SLE) patients. Concentrations in plasma of CL‐L1, CL‐K1, mannan‐binding lectin (MBL), M‐ficolin, H‐ficolin and L‐ficolin were determined in 58 patients with SLE and 65 healthy controls using time‐resolved immunoflourometric assays. The SLE patients' demographic, diagnostic, clinical and biochemical data and collection of plasma samples were performed prospectively during 4 months. CL‐L1, CL‐K1 and M‐ficolin plasma concentrations were lower in SLE patients than healthy controls (P‐values < 0·001, 0·033 and < 0·001, respectively). H‐ficolin concentration was higher in SLE patients (P < 0·0001). CL‐L1 and CL‐K1 plasma concentrations in the individuals correlated in both patients and controls. Patients with low complement component 3 (C3) demonstrated a negative correlation between C3 and CL‐L1 and CL‐K1 (P = 0·022 and 0.031, respectively). Patients positive for anti‐dsDNA antibodies had lower levels of MBL in plasma than patients negative for anti‐dsDNA antibodies (P = 0·02). In a cross‐sectional cohort of SLE patients, we found differences in the plasma concentrations of CL‐L1, CL‐K1, M‐ficolin and H‐ficolin compared to a group of healthy controls. Alterations in plasma concentrations of the PRMs of the lectin pathway in SLE patients and associations to key elements of the disease support the hypothesis that the lectin pathway plays a role in the pathogenesis of SLE.